RELATIONSHIP OF PREMATURE RUPTURE OF MEMBRANES (PROM) WITH NEONATORY ASPHYSIA IN SANTA ELISABETH HOSPITAL BATAM CITY - Roni Aldiano; Fitta Deskawati (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2021)
The high rate of infant mortality is caused by many factors, including neonatal asphyxia and premature rupture of membranes. KPD followed by infection can increase perinatal morbidity and mortality. Asphyxia is a newborn emergency in the form of respiratory depression that continues, causing various complications. This study aims to determine the relationship between premature rupture of membranes and Asphyxia Neonatorum. Method : The research method used was an analytic survey with a cross sectional approach. Conducted at the ST Hospital. Elisabet, the study was conducted for 6 months, the population in this study were all patients in the delivery room with term delivery at Santa Elisabeth Hospital, Batam City from January to December as many as 1,018 people. The sample in this study was 91 people. The sampling technique was carried out by systematic random sampling technique with research instruments using checklists. Data analysis using Chi square. Result :The results of the study with a sample of 91 in 32 mothers with KPD, showed 20 neonates (62.5%) were not asphyxia and 12 neonates (37.5%) had asphyxia. Meanwhile, 59 non-KPD mothers whose babies were not asphyxiated were 53 neonates (89.8%) and 6 neonates had asphyxia (10.2%). The analysis results obtained p = 0.004 (<0.05). Conclusion : The conclusion is that there is a relationship between PROM and the incidence of neonatal asphyxia at term delivery at Santa Elisabeth Hospital, Batam City. Research suggestion that efforts to reduce the incidence of KPD can be increased.